2003
DOI: 10.1097/01.brs.0000090839.61893.be
|View full text |Cite
|
Sign up to set email alerts
|

Single Versus Multiple Dose Antibiotic Prophylaxis in Lumbar Disc Surgery

Abstract: These results support the use of single preoperative dose of antibiotics in lumbar disc surgery. This is relevant as many lumbar diskectomy patients are candidates for early hospital discharge. At our institution, no increased risk of infection occurred for the single dose group.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
44
0
2

Year Published

2008
2008
2022
2022

Publication Types

Select...
10

Relationship

0
10

Authors

Journals

citations
Cited by 47 publications
(46 citation statements)
references
References 6 publications
0
44
0
2
Order By: Relevance
“…The majority of available studies of antimicrobial prophylaxis in spinal procedures have used single doses or regimens of <24 hours' duration. 732 There is no high-quality evidence supporting a duration of >24 hours, 782 and some sources recommend only a single preoperative dose. 8,769,778 Pediatric efficacy.…”
Section: Spinal Procedures With and Without Instrumentationmentioning
confidence: 99%
“…The majority of available studies of antimicrobial prophylaxis in spinal procedures have used single doses or regimens of <24 hours' duration. 732 There is no high-quality evidence supporting a duration of >24 hours, 782 and some sources recommend only a single preoperative dose. 8,769,778 Pediatric efficacy.…”
Section: Spinal Procedures With and Without Instrumentationmentioning
confidence: 99%
“…A recent study conducted at our center revealed the incidence of infection to be 2.7% [60]. Clearly, aseptic technique and appropriate antibiotic prophylaxis have dramatically reduced infection rates in the perioperative period [61]. Infection may also occur after lumbar puncture, myelogram, cervical laminectomy, lumbar sympathectomy, discography, chemonucleolysis and other procedures.…”
Section: Postoperative and Iatrogenic Spondylodiscitismentioning
confidence: 98%
“…Notably, no other findings proved significant (e.g., the antibiotic utilized, the dosage protocol, the schedule for redosing antibiotics, and the duration of postoperative prophylactic antibiotics). [103233606771148]…”
Section: Prevention Of Spinal Implant Infectionmentioning
confidence: 99%